Tandem and triple high-dose chemotherapy with autologous stem cell rescue in metastatic breast cancer - Huober, Jens; Schneeweiss, Andreas; Hohaus, Stefan; Wittmann, Gerd; Meyer, Anke; Martin, Simona; Goldschmidt, Hartmut; Bastert, Gunther; Haas, Rainer; Wallwiener, Diethelm (Journal of cancer research and clinical oncology, 1998)
The purpose of this phase II study was to evaluate the therapeutic efficacy and toxicity of a tandem or triple high-dose chemotherapy (HDC) with autologous peripheral blood stem cell transplantation (PBSCT) in patients with metastatic breast cancer (MBC) as first line chemotherapy. Conventional chemotherapy consisted of two cycles of epirubicin 120 mg/m2 and ifosfamide 7500 mg/m2 in the case of tandem HDC and one cycle of paclitaxel 135 mg/m2, epirubicin 90 mg/m2 and ifosfamide 6000 mg/m2 in the case of triple HDC. Tandem HDC was composed of two cycles of epirubicin 180 mg/m2, ifosfamide 12000 mg/m2 and carboplatin 900 mg/m2. In the case of triple HDC, paclitaxel 180 mg/m2, etoposide 1500 mg/m2 and thiotepa 600 mg/m2 was added as the third cycle. Patients with tandem HDC (n = 20) were evaluable for both survival and toxicity, and patients with triple HDC (n = 21) only for toxicity because of short-term follow-up. Both tandem and triple HDC were well tolerated and could be safely administered. Non-hematological WHO grade 3 or 4 toxicities were mucositis (8), temporary renal insufficiency (1), myocardial infarction (1), and neuropathy (1). No toxic death occurred. The Kaplan-Meier estimates for 44-months without progression and the overall survival were 12% and 38% respectively. The median survival was 22 months (95% CI: 7.4-51.7 months) and the median progression-free interval 14 months (95% CI: 5.1-43.7 months). In a population with an unfavorable prognosis, tandem HDC showed similar efficacy as to that described in other phase II studies. Triple HDC seems not to improve patient outcome compared to tandem HDC, but a long-term follow up is required.